Gangguan pendengaran pada sindroma LEOPARD - Zizlavsky, Semiramis; Suwento, Ronny; Alia, Dina (Oto Rhino Laryngologica Indonesiana, 2012)
Background: Leopard syndrome is a rare case, only around 200 cases has been reported worldwide.  Leopard syndrome is abbreviation for multipel Lentigines, Electrocardiographic conduction, Ocular hypertelorism, Pulmonary stenosis, Abnormality of genitalia, Retardation of growth, and sensorineural Deafness. This disorder suggests a possible relation between PTPN11 gene mutations and distinct clinical features. Purpose: This case is presented so that ENT specialists could identify signs and symptoms of Leopard Syndrome which manifest as sensorineural hearing loss (SNHL). Case: We report a 29 year old woman with multiple lentigines, scoliosis and atrial septal defect. She has 4 year old twin boys, one of them has cryptorchidism and a 10 month old girl with asymmetric septal hypertrophy and they also have multipel lentigines. They were referred to ENT Department for auditory function screening since  Leopard syndrome is suspected. The audiometry of the mother reveals mild conductive deafness (40 dB)  in right ear due to tympanic membrane perforation. Audiometry of the twin boys reveals sensorineural hearing loss above 4000 Hz frequency. Brainstem Evoked Response Audiometry (BERA) of the daughter reveals mild sensorineural hearing loss (40 dB )on right ear. Genogram shows that the disorders is dominant autosomal inherited. Management: Periodic auditory examination for sensorineural hearing loss is recommended since delayed onset could occur. Conclusion: Sensorineural hearing loss is a mani-festation of Leopard syndrome that should be assessed early and periodically to detect delayed onset. Keywords: Sensorineural hearing loss (SNHL), Leopard syndrome, generalized lentiginosa.    Abstrak :  Latar belakang: Sindroma Leopard merupakan kasus yang jarang ditemukan dan dari publikasi yang ada, hingga saat ini hanya terdapat 200 kasus di seluruh dunia. Sindroma Leopard merupakan singkatandari Lentigines multipel, Electrocardiographic conduction, Ocular hypertelorism, Pulmonary stenosis,Abnormality of genitalia, Retardation of growth and sensorineural Deafness. Kelainan ini disebabkan olehmutasi gen PTPN11 dengan gambaran klinis yang khas. Tujuan: Kasus ini diajukan agar spesialis THTmengenali gejala sindroma Leopard yang dapat melibatkan gangguan pendengaran berupa sensorineuralhearing loss(SNHL) sehingga tidak terjadi keterlambatan dalam penatalaksanaan. Kasus: Perempuanberusia 29 tahun dengan lentiginosa multipel, skoliosis dan defek septum atrium. Ia memiliki 2 anaklaki-laki kembar yang salah satunya mengalami kriptorkismus dan anak perempuan usia 10 bulan yangmenderita hipertrofi septum asimetris dan juga menderita multipel lentiginosa. Mereka dikonsulkan ke THT dari bagian kulit RSCM untuk pemeriksaan fungsi pendengaran dengan kecurigaan sindromaLeopard. Pada pemeriksaan audiometri diperoleh hasil pada ibu berupa tuli konduktif ringan (40 dB)telinga kanan akibat perforasi membran timpani. Dua orang anak kembar menunjukkan hasil tuli sarafdi atas frekuensi 4000 Hz. Pemeriksaan Brainstem Evoked Response Audiometry (BERA) pada anakperempuan menunjukkan tuli saraf ringan (40 dB) di telinga kanan. Genogram menunjukkan kelainanautosom dominan. Penatalaksanaan: Tindak lanjut berupa pemeriksaan pendengaran secara berkaladianggap penting untuk mendeteksi terjadinya awitan lambat. Kesimpulan: SNHL merupakan salah satumanifestasi sindroma Leopard yang perlu diperiksa untuk mendeteksi terjadi awitan lambat. Kata kunci: Sensorineural hearing loss (SNHL), sindroma Leopard, lentiginosa multipel.